Geology and Nickel-Laterite Weathering Deposit in the Southeast Arm of Sulawesi - Suratman Suratman (Berita Sedimentologi, 2000)
Nickel-laterite deposits are derived from ultrabasic bedrock after undergoing prolonged chemical erosion at a greater rate than mechanical erosion. In describing the origin of Ni-laterites, it is logical to proceed from a consideration of the bedrock type and their origin in order to define the occurrence and distribution in space and time, prior to determining favorable weathering environment and detail profiles of its mineralogical and chemical conditions.Principal occurrences of Ni-laterites in Sulawesi coincide with two northwest trending belts of ultrabasic rock and derived sediments. The first trend is the southwest belts from Sua-sua through Pomalaa and Torobulu to the island of Wawoni. The second trend is the northeast belt runs from Malili and Kolonodale at north end of the arm to Lasolo on the east coast.